THE PROFILE OF DISTAL RADIUS FRACTURE COLLES’ TYPE AT DR. SOETOMO HOSPITAL IN 2013 - Devina Gabriella Nugroho; Sulis Bayusentono; Nancy Margaritta Rehatta (Journal Orthopaedi and Traumatology Surabaya, 2017)
The fracture cases become increase because the rapid development of transportation and human mobility today is not offset by good vigilance in conducting the activity. One of the most common location is in the hand and involves distal radius part, named Colles’ fracture. Colles’ fracture is the most common wrist fracture (almost 80% of the forearm fractures and the incidence rise in elderly people especially woman. The adequate distribution data of Colles’ Fracture is not available yet. If this situation keeps going, it will have impacts on the lack of preventive measures and recovery methods. The study was design as descriptive and used secondary data from medical records in Orthopedics and Traumatology Department of Dr. Soetomo Hospital Surabaya. Total 37 patients that included in inclusion criteria. Distal radius fracture Colles’ type was common in woman. The most common age was 45-64 years old. Most common causes of fracture was traffic accidents. Left forearm become major affected side. The incidence dominantly occurred at the street. The incidence often occurred at 12.00-18.00. The onset of admission from the incidence place to hospital was less than 8 hours.